Ommatoiulus ktarii, a new millipede from Tunisia and considerations on the taxonomy of the genus (Diplopoda, Julida, Julidae) - Akkari, Nesrine; Reip, Hans (Zootaxa, 2023)
A new millipede, Ommatoiulus ktarii sp. nov., is here described from Tunisia based on relatively recently collected specimens from the semi-arid area of the plain of Oueslatia. A description of the external morphology and gonopod structures are provided, proving the new species to be most similar to the only hitherto known schizophyllinine from Libya, Ommatoiulus rimosus (Karsch, 1881) described more than 140 years ago. Photographs of the gonopods of all Tunisian Ommatoiulus Latzel, 1884 species are provided.